Action research on addressing the negative impacts of informal economy in an online micro food business: Using the legalist approach and motives theories towards the goal of sustainability and growth - Dumlao, Patrisha Anne C. (Animo Repository, 2021)
This action research is about addressing the negative impacts of operating under the informal economy and how it inhibits an online micro food business to achieve sustainable growth. Established during the peak of the COVID-19 pandemic in June 2020, Nini’s Oven began with zero plans and was launched overnight. However, albeit the business’s continued increase in demand month on month since it started, there are still a lot of aspects that limit its growth. With the help of a system mapping tool, it was identified that all manifestations of the issues were brought about by the informal nature of business. Guided by the Legalist Approach and Motives theories, as well as essential strategic management frameworks, and with the help of the collaborators, this action research had been successful in helping Nini’s Oven to graduate out of informality. The first cycle of this action research addressed the inefficient production brought by the limited capacity and manpower of the company. The crucial steps completed in this cycle were official business registration and acquisition of a formal address. However, upon the business’s move, the lack of formal standard operating procedures and rules and regulations of the company became more apparent—these focal issues were addressed in the second cycle. Since the action points taken were broad and complex, the Covey’s Matrix was utilized in identifying important action points, while the process of change had been guided by McKinsey’s 7S Framework. Overall, the interventions made have helped trigger the micro business to take the first few crucial steps towards achieving its desired growth and planning for sustainability.